Optimization of multi-tooth milling tool for interlaminar damage suppression in the milling of carbon fiber–reinforced polymers - Liu, Jian; Tang, Xinkai; Li, Shipeng; Qin, Xuda; Li, Hao; Wu, Weizhou; Srijana, Yadav; Liu, Wentao; Liu, Haibao (Springer, 2022)
Carbon fiber–reinforced polymers (CFRP) are widely utilized in the aerospace field due to their significant specific strength, specific modulus, and strong design ability. However, anisotropy and low interlaminar bonding strength lead to burr, tear, lamination, and other damages in CFRP machining. In this paper, a 3D finite element model for the milling of CFRP was carefully developed, and the cutting forces, the interlaminar stress, and the interlaminar damage were properly obtained. Typically based on the developed model, the effects of geometric parameters of the multi-tooth milling tool were precisely analyzed. Next tool geometries were optimized for suppressing the interlaminar damage in the milling of CFRP. Results convincingly show that the multi-tooth milling tool with the geometry of 1.4 mm length of the micro tooth, 38.2° left helix angle, 11 left-handed chip grooves, 15° right helix angle, 12 right-handed helix grooves, approximately rectangular of section shape of the chip groove, 10° rake angle, and 15° clearance angle efficiently delivers the optimal performance. Besides, cutting performance of numerous coated tools was also studied. Results typically show that the multi-tooth milling tool with a diamond coating maintains significant advantages in aspects of the tool life and costs compared with the uncoated and diamond-like carbon coating (DLC)-coated tools.
Keywords: CFRP; Multi-tooth milling tool; Optimization; Interlaminar damage suppression